Adoption of biodegradable mulching films in agriculture: is there a negative prejudice towards materials derived from organic wastes? - Scaringelli, Myriam Anna; Giannoccaro, Giacomo; Prosperi, Maurizio; Lopolito, Antonio (Italian Journal of Agronomy, 2016)
During the last years ongoing research has moved towards the valorisation of organic waste by the identification of possible products with a good market perspective. In this paper we consider the possibility of using the organic fraction of municipal waste to produce biodegradable mulching films for agricultural purposes. The aim of this research was to estimate the potential demand of horticultural farms located in the province of Foggia (Italy) for biodegradable films derived from organic waste. We carried out a survey of 107 producers in the area. Findings showed that the adoption of the innovative films does not depend on the nature of the raw material used and that the willingness to pay for such films is higher with respect to the price of similar products already available in the market. In addition, farmers’ preferences towards mulching films’ attributes (strength, durability, mechanical harvesting, transparency, etc.) are identified.